In Vivo Evaluation of a Gastro-Resistant Enprotect® Capsule under Postprandial Conditions - Grimm, Michael; Rump, Adrian; Kromrey, Marie-Luise; Morof, Felix; Dumont, Camille; Jannin, Vincent; Tzvetkov, Mladen Vassilev; Weitschies, Werner (Pharmaceutics, 2023)
Ready-to-fill enteric hard capsule shells are an evolving field of oral drug and nutraceutical products. Lonza Capsugel® Enprotect® capsules were recently proven to provide reliable release in the small intestine after fasted intake, but robustness against postprandial intake needed to be proven. In this study, the capsules were administered to 16 healthy young subjects after intake of a light meal. The Enprotect® capsules were labelled with 5 mg black iron oxide and 25 mg 13C3-caffeine. Magnetic Resonance Imaging was used to identify the localization and visual dispersion of the capsule filling. The salivary appearance of caffeine was considered a second independent and sensitive marker for the initial release. Whereas the fasted gastric residence time of the capsules amounted to 43 ± 32 min, it was increased to 158 ± 36 min after postprandial intake. Therefore, the mean dispersion time according to MRI and the mean caffeine appearance time were increased to 196 ± 37 min and 189 ± 37 min, respectively. But, similar to fasted administration, no capsule disintegration or leakage was observed in the stomach and 38% of the capsules disintegrated in the jejunum and 62% in the ileum. The mean dispersion time after gastric emptying and the mean caffeine appearance time after gastric emptying amounted to 38 ± 21 min and 31 ± 17 min, respectively. Both did not relevantly change compared to the fasted intake. Only the absolute dispersion time and caffeine appearance were prolonged due to the increased gastric residence and no relevant influence of the light meal was observed on the disintegration or release behavior of Enprotect® capsules after gastric emptying. The capsules also showed robust enteric properties after postprandial administration.